Three fold system (3FS) for mental health domain - Hadzic, Maja; Cowan, Roberta (Springer, 2007)
Abstract: Along with an increase in the number of mentally ill people, research into all aspects of mental health has increased in recent years. In all disciplines information is the key to success but major problems adversely affect the efficiency and effectiveness that available mental health information is used. These relate to the lack of existing infrastructure to support effective access and information retrieval, and lack of tools to analyze the available information and derive useful knowledge from it. In this paper we explain how the ontology, multi-agent system and data mining technologies can be implemented within the mental health domain to effectively address these issues. The synergy of these frontier technologies may result in an intelligent information infrastructure that provides effective and efficient use of all available information.